Precision grinding for rapid fabrication of segments for extremely large telescopes using the Cranfield BoX - Tonnellier, Xavier; Morantz, Paul; Shore, Paul; Comley, Paul (International Society for Optical Engineering; 1999, 2012)
An ultra precision large optics grinding machine, BoX®, was developed and produced at Cranfield University. BoX® offers a rapid and economic solution for grinding large off-axis aspherical and free-form optical components. Grinding high accuracy surfaces with low subsurface damage reduces subsequent polishing time. This efficient grinding process provides the capacity to grind 1.5 m parts. This paper presents an analysis of Astrositall® optical ground parts: a hexagonal 84 m radius of curvature mirror of 1 m across corners and an off-axis 350 mm diameter mirror. The 1 m hexagonal part is representative of segments under study for making extremely large telescope (ELT) segmented mirrors. The second part was machined off-axis to demonstrate free-form fabrication capability. These operations demonstrate the scalability of the rapid grinding process developed for large free-form optics. The use of an error compensation procedure improved an initial ground form accuracy to +/- 1 μm p-v over 1 metre surface. The results highlighted the effect of grinding parameters and machine dynamics on form accuracy and fabrication t